1997
DOI: 10.1046/j.1365-3083.1997.d01-406.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered IL‐1β and IL‐2 mRNA Expression in Murine Splenic Cells After Concomitant Stimulation by Semliki Forest Virus and Lipopolysaccharide

Abstract: Yang J, Hukkanen V, Seljelid R, Salmi AA. Altered IL-1b and IL-2 mRNA Expression in Murine Splenic Cells After Concomitant Stimulation by Semliki Forest Virus and Lipopolysaccharide. Scand J Immunol 1997;45:349-353 Co-infection with virus and bacteria happens frequently and often results in an exacerbated clinical course of the disease, possibly due to mechanisms including altered cytokine production. In the present study, the authors investigated the combined effects of avirulent Semliki Forest virus (SFV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It has been shown that the expression of cytokine mRNA in naive mice or in the early phase of EAE induction is either undetectable or very low [6, 19, 20]. Likewise, we have shown earlier that IL‐1β and IL‐2 mRNA expression by splenic cells from naive mice in vitro is minimal [21]. In the present study, we observed that the remission of disease in our CR‐EAE model was associated with an increased expression of IL‐2 and IFN‐γ in LNs and a decreased expression of IL‐10 in the spleen (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…It has been shown that the expression of cytokine mRNA in naive mice or in the early phase of EAE induction is either undetectable or very low [6, 19, 20]. Likewise, we have shown earlier that IL‐1β and IL‐2 mRNA expression by splenic cells from naive mice in vitro is minimal [21]. In the present study, we observed that the remission of disease in our CR‐EAE model was associated with an increased expression of IL‐2 and IFN‐γ in LNs and a decreased expression of IL‐10 in the spleen (Fig.…”
Section: Discussionmentioning
confidence: 72%